Conhecimento em nutrição de merendeiras das escolas de ensino infantil e fundamental da rede Pública da cidade de Pelotas /RS - Leal, Cynthia Munhoz dos Anjos (2011)
Introduction: the healthy food is a well-known important factor to maintain health. The inadequate food associated to other determinants is responsible for the incidence of chronic-degenerated diseases in the different population subgroups (adults, adolescents, workers). It still is polemic in the literature the importance of nutritional knowledge to adhere to healthy eating habits. Objective: to describe the level of knowledge about nutrition and the frequency of healthy eating habits in primary and elementary public school cooks in Pelotas. Methodology: it will be a census cross-sectional observing cohort study. The studied population will be cooks working in the preparation and distribution of school food in primary and elementary public schools in the urban area in Pelotas,RS. To collect data it will be used a questionnaire with social economic, demographic, food and health questions. To verify the level of knowledge about nutrition, a specific questionnaire will be applied. The statistic analysis will be performed using SPSS 17.0 statistic software.